Efficacy of Short-Term Estrus Synchronization Protocols and Timed Artificial Insemination in Subtropical Goats - S. M. H. Andrabi; M. Anwar; A. Mehmood (Journal of Animal and Plant Sciences, 2015)
The present study was performed to assess the efficacy of two short-term estrus synchronization protocols at farm vs. field conditions in subtropical goats (n=39) during peak breeding season. Group one was treated with double IM injection of 75 µg cloprostenol (prostaglandin F2 alpha analogue) at 9 days interval. In group two, estrus was synchronized with injection of 25 mg progesterone (IM), and an injection of cloprostenol at 9 days interval. Timed artificial insemination (TAI) was conducted after 48 h of last cloprostenol injection, followed by 2nd TAI after 12 h with chilled semen. Pregnancy test was performed with ultrasonography at 45 days post-insemination. Estrus was induced in all the animals (100%), irrespective of treatment (double cloprostenol vs. progesterone + cloprostenol) or location (farm vs. field). Treatment and location did not affect estrus onset, estrus duration, pregnancy rate, kidding rate and litter size (p>0.05). However, a trend was evident from the overall values that there was a narrower range in double cloprostenol than progesterone + cloprostenol treated groups in estrus onset (24-37 h vs.18-48 h) and estrus duration (36-60 h vs. 24-96 h). Similarly overall pregnancy rate (78.9% vs. 55%) and kidding rate (68.4% vs. 45%) were higher in double cloprostenol treated does as compared to the progesterone + cloprostenol treated group. In conclusion, the two short-term estrus synchronization protocols evaluated in the present study can be used in subtropical goats during the peak breeding season.
Keywords: Estrus synchronization; TAI; goats; subtropical